1970
DOI: 10.1136/jnnp.33.4.438
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus intensity and site of excitation in human median nerve sensory fibres

Abstract: SUMMARY Median nerve sensory fibres were stimulated with minimal and supramaximal stimuli at the base of the third digit in 30 normal subjects. Evoked nerve action potentials were simultaneously recorded from two points on the median nerve just above the wrist. As stimulus voltage was increased from minimal to supramaximal, amplitudes of nerve action potentials increased, latencies decreased, but conduction velocities remained unchanged. The shortening of latencies was interpreted as movement of the effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

1976
1976
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…However, it also suggests that with increasing stimulus intensity, participants begin to report words related to thin fibers. This could be either due to recruitment of small-diameter fibers -which is in accordance with has been seen for pulse stimulation [10,11] but not for sinusoidal stimuli [24] -or discomfort perceived due to the higher intensities. In addition, studies with laser stimuli (i.e., used to assess nociceptive conduction) have shown that after stimulation there is a profile of alpha ERS followed by ERD, at the primary somatosensory, parasylvian and medial frontal cortices [28], which differs from the profile observed in the present study.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…However, it also suggests that with increasing stimulus intensity, participants begin to report words related to thin fibers. This could be either due to recruitment of small-diameter fibers -which is in accordance with has been seen for pulse stimulation [10,11] but not for sinusoidal stimuli [24] -or discomfort perceived due to the higher intensities. In addition, studies with laser stimuli (i.e., used to assess nociceptive conduction) have shown that after stimulation there is a profile of alpha ERS followed by ERD, at the primary somatosensory, parasylvian and medial frontal cortices [28], which differs from the profile observed in the present study.…”
Section: Discussionsupporting
confidence: 56%
“…Electric pulse stimulus has also been extensively used with this purpose, [9] and although it has been reported that it seems to evoke tactile perception artificially in a given intensity [9], it is known that it provides recruitment of thick fibers firstly (Aβ) and thin fibers in a second moment (Aδ and C), especially with increasing stimulus intensities [10,11]. Selectively activating Aβ-fibers could be rather useful for disease evaluation -i.e., diagnosis and progression of conditions that involve sensorial and tactile loss, such as stroke, diabetes mellitus, phantom limb pain and leprosy [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Another relevant factor to reliably detect SEP components is the distinctiveness of the components which depend on the SEP amplitude and current intensity . Sarica et al could demonstrate that a current intensity of at least 1.5*CPT was needed to generate a LUTSEP.…”
Section: Discussionmentioning
confidence: 99%
“…Another relevant factor to reliably detect SEP components is the distinctiveness of the components which depend on the SEP amplitude and current intensity. 7,16 Sarica et al 7 could demonstrate that a current intensity of at least 1.5*CPT was needed to generate a LUTSEP. However, even with a current intensity of 2*CPT, peak detection was not fully unambiguous, similar to the example shown in Figure 3B.…”
mentioning
confidence: 99%
“…The latency (even e assistance when the rise itime of the action potential is taken occasional into account) was longer than that to the onset be readily of the maximum H reflex in that individual, but ntial amplithis might be expected. The effective site of ge reported stimulation may depend on stimulus intensity (Wiederholt, 1970). Group I volleys near threshold which was may first activate smaller motoneurones whose axons have slower conduction velocities than the motoneurones activated by a maximum group I '.a;…”
Section: Discussionmentioning
confidence: 99%